Characterization of food web structure of the upper continental slope of the Celtic Sea highlighting the trophic ecology of five deep‐sea fishes. (16th November 2017) - Kopp, D.; Robert, M.; Pawlowski, L.
Summary: In marine ecosystems, the study of trophic relationships has extensively benefited from the development of stable isotope analyses (SIA) as dietary tracers. SIA are particularly useful in elucidating the structure of deep sea food webs given the constraints involved in obtaining gut‐content data from deep trawling. We used carbon and nitrogen stable isotope analyses and Stable Isotope Bayesian Ellipses in R (SIBER) and Stable Isotope Analysis in R (SIAR) routines, to determine the trophic ecology of five deep‐sea fishes from the upper continental slope of the Celtic Sea. SIA made it possible to deduce some general tendencies in food‐web structure and species trophic interactions and confirmed diet determined by gut‐content analysis for the same species, in other ecoregions. More specifically, mixing models revealed that the deep sea species considered are omnivorous and are able to feed on all the sampled taxa. Based on isotopic ratio, no clear differences in fish diet could be detected from one species to another except for rabbit fish, which has benthic affinities. Three species, blackbelly rosefish, greater forkbeard and softhead grenadier showed overlapping isotopic niches. This study is the first attempt to describe the trophic ecology of deep sea species on the Celtic Sea upper continental slope. In the context of the development of ecosystem integrated modeling approaches for managing fisheries in the Celtic sea, and considering the vulnerability of deep‐water species, improving the knowledge on the trophic ecology of these local species is of importance in order to allow their sustainable exploitation.